UJI EFEKTIVITAS METODE PEMBUATAN BIOKERAMIK CANGKANG TELUR MENGGUNAKAN SODIUM ALGINAT DAN PATI JAGUNG - Khalyla Hafsa Khairunnisa; Mustofa Kamal, Dianta; Djonaedi, Emmidia (UIR Press, 2025)
The utilization of eggshell waste in Indonesia is still very low, which is only around 7-8% of the total waste of 611,790 tons per year, although the calcium carbonate content has the potential to be used as a raw material for bioceramics. Suboptimal utilization risks polluting the environment. This study aims to develop the utilization of eggshell waste into bioceramics by comparing the effectiveness of two types of binders, namely sodium alginate and corn starch. The manufacturing method includes the process of powdering eggshells, mixing with binders, molding, and drying. Evaluation is carried out through density testing, water absorption, and degradation tests in water. The results showed that bioceramics with corn starch had a higher density (2.05 g/m³), lower water absorption (34.5%), and neutral pH of the degradation water (pH 7), compared to sodium alginate which had a lower density and higher absorption (50.5%) with pH 8. These findings indicate that corn starch is superior in forming stable and solid bioceramics, so it has the potential to be applied in environmentally friendly craft products and supports the reduction of organic waste in the community.